Development policy based on local assistance - Iriawan, Hermanu; Edyanto, Edyanto (International research journal of management, IT and social sciences, 2021)
This study aims to determine local wisdom-based development policies in Bintuni Bay Regency. The data collection techniques used were; observation, interview, and documentation. The analytical method used is qualitative analysis. The results showed that Development policies in Bintuni Bay Regency always pay attention to the aspirations of the 7 Tribes in Bintuni Bay Regency. Therefore, every policy in Teluk Bintuni Regency always maintains the local wisdom of the 7 major tribes in Bintuni Bay Regency. The Regional Government of Teluk Bintuni Regency in formulating policies always involves the aspirations of 7 major tribes in Bintuni Bay Regency.